2020
DOI: 10.1186/s12866-020-1711-4
|View full text |Cite
|
Sign up to set email alerts
|

The C3HC type zinc-finger protein (ZFC3) interacting with Lon/MAP1 is important for mitochondrial gene regulation, infection hypha development and longevity of Magnaporthe oryzae

Abstract: Background: The rice blast is a typical fungal disease caused by Magnaporthe oryzae, and the mitochondrial ATPdependent Lon protease (MAP1) has been proven to be involved in blast development. We previously screened a C3HC type Zinc-finger domain protein (ZFC3), which is interacted with MAP1. The purpose of this research was to study the biological function of ZFC3 protein in M. oryzae. Results: We first confirmed that the ZFC3-RFP fusion protein is localized within the mitochondria. The deleted mutant strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…The result showed that the content of ATP in mycelia and conidia of Δ MoCA1 strain was lower than wild-type and Δ MoCA1/MoCA1 strains ( Figure 5E ), indicating that the loss of MoCA1 affects the energy metabolism in the mutant strain, which, in turn, affects the synthesis of intracellular ATP. Furthermore, when ATP synthesis genes expression level of mtATP6 (GenBank: MGG_21007), mtATP8 (GenBank: MGG_21008), and nATP9 (GenBank: MGG_00892) was checked using qRT-PCR ( Liu et al, 2020 ), the results showed that ATP synthesis genes were significantly downregulated in Δ MoCA1 mutant ( Figure 5F ). From these results we confer, that MoCA1 is involved as a positive regulator in ATP synthesis and energy metabolism in mitochondria of M. oryzae .…”
Section: Resultsmentioning
confidence: 99%
“…The result showed that the content of ATP in mycelia and conidia of Δ MoCA1 strain was lower than wild-type and Δ MoCA1/MoCA1 strains ( Figure 5E ), indicating that the loss of MoCA1 affects the energy metabolism in the mutant strain, which, in turn, affects the synthesis of intracellular ATP. Furthermore, when ATP synthesis genes expression level of mtATP6 (GenBank: MGG_21007), mtATP8 (GenBank: MGG_21008), and nATP9 (GenBank: MGG_00892) was checked using qRT-PCR ( Liu et al, 2020 ), the results showed that ATP synthesis genes were significantly downregulated in Δ MoCA1 mutant ( Figure 5F ). From these results we confer, that MoCA1 is involved as a positive regulator in ATP synthesis and energy metabolism in mitochondria of M. oryzae .…”
Section: Resultsmentioning
confidence: 99%
“…High levels of reactive oxygen species (ROS) generally damage cells causing premature ageing (Harman, 1972; Tsilibaris et al ., 2006; Cui et al ., 2017). Lon proteases and/or their substrates are also associated with senescence or ageing in fungi (Cui et al ., 2015; Liu et al ., 2020). By measuring the continuous growth of hyphae on solid media plates, the lifespan and senescence of the four transgenic strains (Δ PrePL/PrePL , Δ PrePL/Pc , Δ PrePL and Δ PrePL/PrePL ΔTL/NQ ) were compared with the wild‐type strain using 20‐day culture cycles.…”
Section: Resultsmentioning
confidence: 99%
“…Lon proteases are highly conserved ATP‐dependent proteases that are important for various cellular processes, including growth, reproduction and pathogenicity in prokaryotes and eukaryotes (Tsilibaris et al ., 2006; Coleman et al ., 2009; Li et al ., 2014; Cui et al ., 2015; Liu et al ., 2020). In bacteria, the type III secretion system translocates effector proteins into the cytoplasm of host cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…oryzae , MoCA1 participates in appressorium maturation and morphogenesis; it was found that the loss of the gene reduced melanin synthesis and infection ability [ 61 ]. C3HC type Zinc-finger protein (ZFC3) and deletion of this gene led to increased melanin synthesis and its ability to infect rice cells [ 71 ]. These results suggest that M .…”
Section: Discussionmentioning
confidence: 99%